A Winnicottian Approach to Biblical Lament: Developing a True Self in the Midst of Suffering - Torr, Stephen C. (Journal of psychology and theology, 2019)
There is a growing awareness within Christian scholarship and practice that the biblical theology and practice of lament is not outdated but rather of vital importance for the health of the church in how it relates to God, others, and the self. What this article seeks to explore in a fresh way is why lament is so important by examining how the practice of it achieves the health that is so desperately needed. At the heart of this exploration is a rereading of the biblical lament tradition through the pioneering work of Object Relations Theory psychiatrist Donald Winnicott. A key aspect of Winnicott's work was how the "true self" develops, and it is his work around this subject that is used here to enable exploration of how lament may achieve the development of the true self, rather than a "false self" in the life of those lamenting. It is intended that this will throw fresh light on the theology and practice of lament as well as giving new impetus to Christian communities to consider how they respond to those suffering in their midst.